Investigation on sensing mechanism of a fluorescent probe for TNP detection in aqueous solution. Issue 21 (24th May 2018) - Ma, Yinhua; Zhao, Li; Li, Yang; Liu, Jianyong; Yang, Yanqiang; Chu, Tianshu
Abstract: In this paper, the synthesis and spectral properties of a fluorescent probe Nph-An for TNP detection has been introduced and its sensing mechanism has been studied with density functional theory (DFT) and time-dependent density functional theory (TD-DFT) methods. For TNP detection in aqueous solution the probe shows high sensitivity, selectivity and efficiency. The theoretical results demonstrate that the excited-state intermolecular hydrogen bonding (HB) plays an important role for the TNP detection. In the excited state, the intermolecular HB between Nph-An and TNP is strengthened, and thus strongly facilitates the nonirradiative PET process to induce the fluorescence quenching. Whereas, the probe Nph-An emits strong fluorescence because of the intramolecular charge transfer (ICT) properties, which is confirmed by the solvatochromism effect. The calculated absorption spectra of Nph-An and Nph-An + TNP agree well with the experimental values and theoretical analysis provides a detailed and clear explanation of the sensing mechanism. Graphical abstract: